A Preliminary Study Examining Self-Reported Invincibility, Alcohol Problems, and the Nonmedical Use of Prescription Stimulants in College Students - Kennedy, Susan (Journal of drug issues, 2022)
The nonmedical use of prescription stimulants (NMUPS) is becoming more common among college students. Identifying the variables associated with NMUPS is important for educational efforts and to promote wellness in vulnerable students. The present study examined the relationships between self-reported invincibility, alcohol problems, and NMUPS in 175 college students. Path analysis tested the hypotheses that males would report higher invincibility that would be related to alcohol use and alcohol problems. Using structural equation modeling, significant relationships were found between invincibility and alcohol-related problems. Alcohol problems may be related to NMUPS. A total effect of invincibility, mediated by alcohol use, may be a path whereby invincibility positively influences NMUPS. Students reporting high levels of invincibility may be at risk for the NMUPS and might benefit from efforts regarding the potential harmful consequences of taking these substances without a prescription.